Client service communication’s audit through digital communication at Indonesia communications - Ayu Larasati; Puji Lestari (The Indonesian Journal of Communication Studies, 2022)
During the COVID-19 pandemic, the Indonesian government implemented policies which required people to work, pray, and study from home or a Work From Home (WFH). Such policies are also carried out by ID COMM to serve clients. Thus, this unprecedented phenomenon changed its communication system. This communication audit research is being conducted, to evaluate the flow of communication that occurs to serving clients in ID COMM. The data that was used for this study is taken from interviews and observation through qualitative methods and literature review. As an agency, ID COMM uses transactional communication Tubbs model. ID COMM encountered some problems while doing its job, such as lack of personal touch and less flexibility when presenting both briefs and work. As a result of that effect on revision frequency. Sometimes, another problem that is encountered by ID COMM, the connection is not that good and also the clients just didn’t understand what PR needs for strategy. However, the client is satisfied with the performance of ID COMM in general.